1988
DOI: 10.1007/bf00381078
|View full text |Cite
|
Sign up to set email alerts
|

rCBF landscapes during motor performance and motor ideation of a graphic gesture

Abstract: The regional cerebral blood flow (rCBF) distribution was measured by 133xenon inhalation using a gamma camera in 18 right-handed volunteers, 6 subjects performing a graphic task (writing numbers in letters) with the right hand, 6 subjects imagining the same task, and 6 subjects were assessed during two rest periods to determine the reproducibility of the technique. The mean rCBF increased between 10% and 25% (P less than 0.01) during both motor performance and motor ideation. However, there were regional diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
2

Year Published

1989
1989
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 98 publications
(39 citation statements)
references
References 20 publications
0
37
0
2
Order By: Relevance
“…On the one hand, beginning with the work of Roland, Skinhoj, Lassen & Larsen, (1980), two decades of functional neuroimaging studies have demonstrated that imagining movements activates areas involved in motor planning and control including: cerebellum and basal ganglia (e.g. Decety, Philippon & Ingvar, 1988;Parsons et al, 1995), supplementary and pre-motor areas (e.g. Decety et al, 1994;Deiber, Ibanez, Honda, Sadato, Raman & Hallett, 1997;Parsons et al, 1995;Rao et al, 1993), posterior parietal cortex (e.g.…”
Section: Relationship Between Motor Imagery and Motor Planningmentioning
confidence: 99%
“…On the one hand, beginning with the work of Roland, Skinhoj, Lassen & Larsen, (1980), two decades of functional neuroimaging studies have demonstrated that imagining movements activates areas involved in motor planning and control including: cerebellum and basal ganglia (e.g. Decety, Philippon & Ingvar, 1988;Parsons et al, 1995), supplementary and pre-motor areas (e.g. Decety et al, 1994;Deiber, Ibanez, Honda, Sadato, Raman & Hallett, 1997;Parsons et al, 1995;Rao et al, 1993), posterior parietal cortex (e.g.…”
Section: Relationship Between Motor Imagery and Motor Planningmentioning
confidence: 99%
“…Their results thus confirmed that the SMA plays an important role for the internal programming and simulation of complex motor sequences. Measuring rCBF with mXenon and a gamma camera, Decety, Philippon and Ingvar [2] studied normal subjects during the execution or during the imagination of a graphic movement (writing 'one, two, three, etc.') either with the right or the left hand.…”
Section: Measurements Of Regional Cerebral Blood Flowmentioning
confidence: 99%
“…Subsequent studies employed different methods (SPECT, PET, functional MRI) and various tasks of ISM. It was consistently reported that SMA is active with internal simulation of movements but MI is not active [8,9,11,26,28,30]. In addition to SMA other parts of the cortex were reported to be active with ISM although with little consistency, possibly due to differences among the tasks employed.…”
Section: Introductionmentioning
confidence: 99%